Phylogenetic classification and genetic insights from the complete mitochondrial genome of Medicago ruthenica - Tian, Yonglei; Wu, Zinian; Tian, Chunyu; Yang, Yanting; Li, Zhiyong (Frontiers in Plant Science, 2025)
IntroductionMedicago ruthenica, an essential wild perennial relative of Medicago sativa, is distributed across Eurasia, with good palatability and strong tolerance to drought, cold, and saline-alkali stress. It is exhibits wide adaptability, and its morphology varies greatly under different environmental conditions. Owing to this rich morphological diversity, the inference of its phylogeny has been controversial. Extensive studies have been conducted on the nuclear and chloroplast genomes of M. ruthenica; however, because of the complexity of the mitochondrial genome, the M. ruthenica mitochondrial genome has not been systematically described.MethodsIn this study, we successfully assembled the M. ruthenica mitochondrial genome and investigated various related aspects, including genomic features, RNA editing sites, codon preference, gene transfer events, phylogeny, selective pressure, nucleotide diversity analysis and collinearity analysis.Results and discussionThe mitogenome of M. ruthenica is a circular DNA molecule measuring 354,988 base pairs (bp) in length and has a GC content of 45.13%. The mitochondrial genome of M. ruthenica includes 55 genes, with 34 being unique protein-coding genes (PCGs) (excluding three likely pseudogenes), along with three ribosomal RNA genes and 18 transfer RNA genes. The mitogenome is abundant with repetitive sequences; a total of 148 dispersed repeats were identified, including 79 palindromic repeats (53%) and 69 forward repeats (47%), without inverted or complementary repeats. Leucine (Leu) was the most frequently occurring amino acid in PCGs at 10.63%, while tryptophan (Trp) was the least frequent at 1.46%. The codon AUU (Ile) had the highest frequency of use, with the relative synonymous codon usage (RSCU) value of 1.29. atp8, atp4, rps4, nad4, ccmB, ccmFc and nad9 showed significant positive selection pressure in multiple legumes (Ka/Ks > 1) Additionally, M. ruthenica’s phylogenetic relationship was categorized under Medicago, supported by mitogenome data from 33 other legume species. Understanding the mitochondrial genome characteristics of M. ruthenica is critical for elucidating its genetic background. The results of this study serve as a basis for the genetic breeding of M. ruthenica.